The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsami.8b01506
|View full text |Cite
|
Sign up to set email alerts
|

Local Conduction in MoxW1–xSe2: The Role of Stacking Faults, Defects, and Alloying

Abstract: Here, we report on the surface conductivity of WSe2 and MoxW1–xSe2 (0 ≤ x ≤ 1) crystals investigated with conductive atomic force microscopy. We found that stacking faults, defects, and chemical heterogeneities form distinct two-dimensional and one-dimensional conduction paths on the transition metal dichalcogenide surface. In the case of WSe2, in addition to step edges, we find a significant amount of stacking faults (formed during the cleaving process) that strongly influence the surface conductivity. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 71 publications
(140 reference statements)
2
28
0
Order By: Relevance
“…As a matter of fact, SBH mapping with nanoscale resolution is required to disentangle the effect of surface (or near surface) defects in the TMD materials from that of metal-induced gap states. To this purpose, the conductive tip of C-AFM has been employed as a nanoscopic metal electrode to record local I-V characteristics on the TMDs surface, from which the SBH was quantitatively evaluated [44,45,69]. Contacting the TMD surface with a sliding metal tip presents the additional advantage of excluding eventual reactions that have been reported at the metal/TMD interface (for some metal species) when the contact is fabricated by evaporation or sputtering [70,71].…”
Section: Schottky Barrier Height Mapping At Metal/tmds Junctionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, SBH mapping with nanoscale resolution is required to disentangle the effect of surface (or near surface) defects in the TMD materials from that of metal-induced gap states. To this purpose, the conductive tip of C-AFM has been employed as a nanoscopic metal electrode to record local I-V characteristics on the TMDs surface, from which the SBH was quantitatively evaluated [44,45,69]. Contacting the TMD surface with a sliding metal tip presents the additional advantage of excluding eventual reactions that have been reported at the metal/TMD interface (for some metal species) when the contact is fabricated by evaporation or sputtering [70,71].…”
Section: Schottky Barrier Height Mapping At Metal/tmds Junctionmentioning
confidence: 99%
“…Recently, Bampoulis et al [69] used C-AFM to characterize the conductivity of a Mo x W 1−x Se 2 alloy at the nanoscale. They observed the segregation of Mo-rich and W-rich domains and demonstrated that these different regions exhibit distinct SBHs values, reflecting the different band structures of WSe 2 and MoSe 2 .…”
Section: Lateral Heterojunctions Of Tmdsmentioning
confidence: 99%
“…Alloying in 2D transition metal dichalcogenides (TMDs) has allowed bandgap engineering and phase transformation, which enables a new series of electronic and photonic devices. Bandgap engineering has been demonstrated in various TMD ternary alloys, including MoS 2(1−x) Se 2x , [1][2][3][4][5][6] WS 2(1−x) Se 2x , [7,8] Mo 1−x W x S 2 , [9][10][11][12][13] and Mo 1−x W x Se 2 [14,15] by adjusting the composition of the elements. A 2H-1T' phase transformation was observed in Mo 1−x Re x Se 2 .…”
Section: Doi: 101002/adma202002548mentioning
confidence: 99%
“…Mechanical exfoliation can consequently induce defect patterns and networks that modify the local electronic structure and chemical reactivity of the basal plane surface. [11][12][13] In principle, the local differences in properties induced by defects can consequently alter the chemical reactivity of the surface. Such heterogeneity can be exploited to produce patterned deposition using defect-selective deposition methods and reaction conditions.…”
Section: D Layered Materials Such As Graphite and Transition Metal mentioning
confidence: 99%